2020
DOI: 10.3390/plants9070864
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mechanisms of Quantitative Resistance to Leptosphaeria maculans (Blackleg) in the Cotyledons of Canola (Brassica napus) Based on Transcriptomic and Microscopic Analyses

Abstract: Using resistant cultivars is a common approach to managing blackleg of canola/rapeseed caused by Leptosphaeria maculans (Lm). Quantitative resistance (QR), as opposed to major-gene resistance, is of interest because it is generally more durable, due to its multi-genetic basis. However, the mechanisms and genes underlying QR are mostly unknown. In this study, potential QR modes of action in “74‑44 BL” was explored. This Canadian canola cultivar showed moderate but consistent race-nonspecific resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…However, visual scoring of lesions on cotyledons or leaves may not provide an accurate measure of pathogen load. In this and other studies, microscopic images of cotyledon colonisation show abundant hyphae invading tissue beyond the visual boundary of the lesion (Huang et al [ 31 ], Hubbard et al [ 43 ]). In turn, hyphal colonisation can be significantly smaller than the areas stained for ROS (Reaction Oxygen Species involved in Programmed Cell Death) such as hydrogen peroxide using 3,3-diaminobenzidine (DAB) (Hubbard et al [ 43 ]).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, visual scoring of lesions on cotyledons or leaves may not provide an accurate measure of pathogen load. In this and other studies, microscopic images of cotyledon colonisation show abundant hyphae invading tissue beyond the visual boundary of the lesion (Huang et al [ 31 ], Hubbard et al [ 43 ]). In turn, hyphal colonisation can be significantly smaller than the areas stained for ROS (Reaction Oxygen Species involved in Programmed Cell Death) such as hydrogen peroxide using 3,3-diaminobenzidine (DAB) (Hubbard et al [ 43 ]).…”
Section: Discussionsupporting
confidence: 58%
“…In this and other studies, microscopic images of cotyledon colonisation show abundant hyphae invading tissue beyond the visual boundary of the lesion (Huang et al [ 31 ], Hubbard et al [ 43 ]). In turn, hyphal colonisation can be significantly smaller than the areas stained for ROS (Reaction Oxygen Species involved in Programmed Cell Death) such as hydrogen peroxide using 3,3-diaminobenzidine (DAB) (Hubbard et al [ 43 ]). The described assays could be used in conjunction with standard visual scoring techniques to provide more precise differentiation of host responses, particularly in the identification of novel sources of genetic resistance that act in the leaf during infection.…”
Section: Discussionsupporting
confidence: 58%
“…Resistance gene analog prediction can also be compared or applied to transcriptomic data (e.g. Lowe et al 2014;Becker et al 2017Becker et al , 2019Hubbard et al 2020;Song et al 2021) and applied across accessions with known resistance responses and large databases such as BnPIR. This latter approach can be particularly useful, considering the high diversity in terms of gene content between accessions, to assess the conservation of a particular candidate resistance gene analog (Song et al 2020).…”
Section: Genomics Methods For Candidate Resistance Gene Predictionmentioning
confidence: 99%
“…For QR, the role of a diverse set of genes has been proposed. In a recent transcriptome profiling experiment, Hubbard et al ( 2020 ) found genes controlling programmed cell death (PCD), reactive oxygen species (ROS) and intracellular endomembrane transport as critical regulators of QR. The ROS burst was coincident with inhibited fungal growth and rapid cell death.…”
Section: Genomics-aided Identification Of Qr Loci and Genesmentioning
confidence: 99%